Ultralong lifetime and efficient room temperature phosphorescent carbon dots through multi-confinement structure design - Yuqiong Sun (Nature Portfolio, 2020)
For room temperature phosphorescence (RTP) materials to reach their potential for optical applications, new materials with improved performance must be realized. Here, the authors report multi-confined carbon dots as high stability RTP materials with long afterglow lifetime & high efficiency.